2021
DOI: 10.1111/mec.15864
|View full text |Cite
|
Sign up to set email alerts
|

Small freshwater ecosystems with dissimilar microbial communities exhibit similar temporal patterns

Abstract: Despite small freshwater ecosystems being biodiversity reservoirs and contributing significantly to greenhouse fluxes, their microbial communities remain largely understudied. Yet, microorganisms intervene in biogeochemical cycling and impact water quality. Because of their small size, these ecosystems are in principle more sensitive to disturbances, seasonal variation and pluri-annual climate change. However, how microbial community composition varies over space and time, and whether archaeal, bacterial and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 105 publications
0
21
0
Order By: Relevance
“…Temporal variability of freshwater bacterial communities has been much less studied than its spatial counterpart although temporal patterns in community composition can be even stronger than those occurring through space (Portillo et al, 2012 ; Veach et al, 2016 ). Some evidence, mainly from lentic environments, suggests that temporal patterns in bacterial communities may be relatively predictable (Shade et al, 2013 ; Veach et al, 2016 ), with annually recurring seasonal variability in community composition (Crump and Hobbie, 2005 ; David et al, 2021 ; Staley et al, 2015 ). Water temperature (Hullar et al, 2006 ; Teachey et al, 2019 ) and river discharge (Fortunato et al, 2012 ) are the key environmental factors reported to underlie seasonal variability in bacterial communities.…”
Section: Introductionmentioning
confidence: 99%
“…Temporal variability of freshwater bacterial communities has been much less studied than its spatial counterpart although temporal patterns in community composition can be even stronger than those occurring through space (Portillo et al, 2012 ; Veach et al, 2016 ). Some evidence, mainly from lentic environments, suggests that temporal patterns in bacterial communities may be relatively predictable (Shade et al, 2013 ; Veach et al, 2016 ), with annually recurring seasonal variability in community composition (Crump and Hobbie, 2005 ; David et al, 2021 ; Staley et al, 2015 ). Water temperature (Hullar et al, 2006 ; Teachey et al, 2019 ) and river discharge (Fortunato et al, 2012 ) are the key environmental factors reported to underlie seasonal variability in bacterial communities.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, in the case of freshwater Etang des Vallées (EdV) samples, mVMR values were at least 3-4 times higher than fVMRs. This difference seems to suggest that, in addition to VPs, intracellular lytic viruses and proviruses were highly prevalent in the freshwater plankton of this highly diverse shallow lake 33 . The ratio of putative proviruses versus cells was indeed of ~3-7 for EdV samples (depending on the annotation strategy) but very low (<0.3) for marine samples, which seems consistent with the prevalent genome streamlining of marine prokaryotes 34 .…”
Section: Estimation Of Mvmr In Aquatic Metagenomesmentioning
confidence: 86%
“…Actinobacteria and Acidobacteria were dominant in soils. Some actinobacterial taxa were also abundant in the freshwater system 33 . Microbial eukaryotes consistently occurred in most ecosystems, albeit in minor proportions.…”
Section: Benchmarking Mvmr In Mock Metagenomesmentioning
confidence: 99%
“…Moreover, microorganisms have a high response rate to changes in environmental conditions, which gives them value as indicators of water quality and ecosystem condition (Ji et al, 2019;Sagova-Mareckova et al, 2021). Therefore, taxonomic and functional changes in microbial communities in lake water can lead to disturbances in ecosystem processes (David et al, 2021;Xie et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The abundance of microorganisms can be determined by natural environmental and climatic factors such as (1) temperature, (2) the degree of photosynthetically active radiation penetration, (3) water salinity, (4) the level of dissolved oxygen, (5) the amount of organic and nutrient substances, etc. (Butler et al, 2019;Yue et al, 2020;David et al, 2021). Therefore, the question of which human activities affect the overall structure and diversity of the microbial community in freshwater lakes remains mostly unknown (Cavaco et al, 2019;Nnadozie & Odume, 2019;Yang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%